Stability of a delay equation arising from ajuvenile-adult model - Azmy S. Ackleh; Keng Deng (Mathematical Biosciences and Engineering)
We consider a delay equation that has been formulated from ajuvenile-adult population model. We give respective conditions onthe vital rates to ensure local stability of the positiveequilibrium and global stability of the trivial equilibrium. We alsoshow that under certain conditions the equation undergoes a Hopfbifurcation. We then study global asymptotic stability and presentbifurcation diagrams for two special cases of the model.